WAYS OF CHANGES IN PROPERTY RIGHTS - Nezir, Funda (International Scientific Journal Vision, 2020)
There are legal transactions that directly affect a right in the property of a person, transferring that right to another person, limiting it, changing or terminating its legal content. With the execution of legal transactions, the absolute and relative rights in the assets of the person are affected, causing changes in the concept of right ownership. Peculium process are usually done to settle a loan that is charged with a debt transaction. Absolute rights, relative rights and legal relationship in assets are among the rights that may be subject to peculium process. In our study, theoretically, in a narrow sense, the effect of legal transactions on assets has been discussed. Based on this scope; The effect of disposition on the right has been examined in terms of the peculium process, the types of affecting the right, and finally the absolute and relative rights in the assets.